2016
DOI: 10.3855/jidc.7695
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance of selected invasive bacteria in a tertiary care center: results of a prospective surveillance study

Abstract: Introduction: We aimed to report the distribution and resistance patterns of eight invasive clinically relevant bacteria surveyed in the Clinical Center of Serbia (CCS) in Belgrade. Methodology: A total of 477 clinical blood stream isolates of Staphylococcus aureus, Streptococcus pneumoniae, Enterococcus faecium, Enterococcus faecalis, Klebsiella pneumoniae, Escherichia coli, Pseudomonas aeruginosa, and Acinetobacter spp. were collected in the period from January to December 2013. Antimicrobial susceptibility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…9,14 On the contrary, few gram-positive cocci in our study were vancomycinresistant, which is similarly reported by Zhu et al 9 Similar to the findings by Djuric et al, the overall resistance among gram-negative isolates was observed highest to β-lactams, trimethoprim-sulfamethoxazole, and aminoglycosides. 13 The MDRI of commonly isolated gram-negative bacilli was alarmingly high and remained consistently high throughout our study period. The resistance pattern is comparable to reports indicating a predictable rise of MDR organisms in the future.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…9,14 On the contrary, few gram-positive cocci in our study were vancomycinresistant, which is similarly reported by Zhu et al 9 Similar to the findings by Djuric et al, the overall resistance among gram-negative isolates was observed highest to β-lactams, trimethoprim-sulfamethoxazole, and aminoglycosides. 13 The MDRI of commonly isolated gram-negative bacilli was alarmingly high and remained consistently high throughout our study period. The resistance pattern is comparable to reports indicating a predictable rise of MDR organisms in the future.…”
Section: Discussionmentioning
confidence: 66%
“…Similar to several studies, gram-negative bacilli were the common isolates (60.2%) in our study. 8,[13][14][15] Gram-positive cocci were the commonly isolated organisms at the beginning of our study in 2013, with CoNS as the frequently isolated group. 16 However, by 2014 onward, upward trend of gram-negative bacilli isolation increased when compared with a decline in the frequency of CoNS isolation.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…and Acinetobacter spp. strains to carbapenems has been previously reported in Serbia in prospective surveillance study within Clinical Centre of Serbia [35] and from CEASAR in 2016 [34]. In contrary, surveillance networks in USA, National Healthcare Safety Network (NHSN) and International Nosocomial Infection Control Consortiu (INNIC) [36,37] and highincome countries of European Antimicrobial Resistance Surveillance Network (EARS-Net) [38] reported considerably lower rates of isolates resistant to common AMR markers, reflecting the differences in measures of primary BSI prevention and control.…”
Section: Discussionmentioning
confidence: 87%
“…A high prevalence of drug resistance microorganisms has been reported. In a study by Djuric et al (2016), more than 95% of the analyzed strains were multidrug resistant, and 65% had an extended spectrum beta-lactamase. All K. pneumonie nosocomial isolates in our study were drug resistant ( Table 1).…”
Section: Discussionmentioning
confidence: 99%